Comparison Of Biofuels In Jet Engine Combustion Characteristic Using Computational Fluid Dynamics - Joanne, Lim Zi Fen (2021)
Rapid decreasing of resources and environmental pollution caused by aviation industries have become a severe issue which leads to increases in the greenhouse effect. The use of biofuel becomes an option to alleviate issues related to unrenewable resources. However, the biofuel is not easy to obtain and experimental work to study biofuels’ performances will be costly. Therefore, computational fluid dynamics (CFD) simulation is a feasible way to study on the biofuel combustion characteristics. This study presents a computational simulation on the biofuel combustion characteristics of various alternative fuels on a real combustion chamber geometry. The biofuels used in this study are biodiesel derived from Sorghum, algae extracted from Spirulina platensis and hydrotreated ester fatty acid types of fuel (HEFA) made from Camelina. Meanwhile, Jet-A is used as a baseline fuel. The fuel properties and combustion characteristics are being investigated and analysed. The results are presented in terms of temperature and pressure profiles in addition to the formation of NOx and soot generated from the combustion chamber. Results obtained show that HEFA fuel is the most recommended biofuel among all four tested fuels as it is being found that it burns with 37.6% lower temperature; 15.2% lower pressure; 89.5% lower NOx emission and 8.1% lower soot emission compared with the baseline fuel. In other words, HEFA fuel burns with relatively high energy and low pollutants.